Unsettled states : nineteenth-century American literary studies - Luciano, Dana; Wilson, Ivy G. (America and the long 19th century., 2014)
In Unsettled States, Dana Luciano and Ivy G. Wilson present some of the most exciting emergent scholarship in American literary and cultural studies of the "long" nineteenth century. Featuring eleven essays from senior scholars across the discipline, the book responds to recent critical challenges to the boundaries, both spatial and temporal, that have traditionally organized scholarship within the field. The volume considers these recent challenges to be aftershocks of earlier revolutions in content and method, and it seeks ways of inhabiting and amplifying the ongoing unsettledness of the f.